2017
DOI: 10.5005/jp-journals-10018-1217
|View full text |Cite
|
Sign up to set email alerts
|

Liver Disease in Sri Lanka

Abstract: Liver disease in Sri Lanka is mainly due to alcoholic liver disease and nonalcoholic fatty liver disease. In contrast to other South Asian countries, the prevalence of hepatitis B and C is low in Sri Lanka and prevalence of hepatitis A is intermediate. The few reported cases of hepatitis E in Sri Lanka are mainly in people who have traveled to neighboring South Asian countries. Wilson’s disease, autoimmune hepatitis, hemochromatosis, drug-induced liver disease, and primary biliary cirrhosis are recognized caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In another study done on 81 patients with cirrhosis who were referred for liver transplantation, none had hepatitis B or C [49]. Even though nationwide data on prevalence of hepatitis C virus (HCV) in Sri Lanka is not available, studies conducted in various specific groups of population have shown a seroprevalence of <1% [46]. Therefore, we assume that not having the serology status would not have made difference to our results.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In another study done on 81 patients with cirrhosis who were referred for liver transplantation, none had hepatitis B or C [49]. Even though nationwide data on prevalence of hepatitis C virus (HCV) in Sri Lanka is not available, studies conducted in various specific groups of population have shown a seroprevalence of <1% [46]. Therefore, we assume that not having the serology status would not have made difference to our results.…”
Section: Discussionmentioning
confidence: 85%
“…We excluded hepatitis by history alone. Hepatitis B infection is not common in Sri Lanka and is not considered a major health problem [46]. Studies conducted on different population groups, including blood donors, pregnant mothers, and prison inmates, have shown prevalence of hepatitis B to be less than 2% [47].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, acute liver failure, though rare, is an important disease entity with very high rates of mortality. In Sri Lanka, alcohol remains a leading cause of liver diseases followed by NAFLD with a relatively lesser burden of chronic viral hepatitis-related liver disease compared to countries in the region and a very low prevalence of hepatitis B and C [4,5]. The prevalence of NAFLD is 18% among rural and 32.6% among urban adult population [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…2 However, it is a rare disease in Sri Lanka and there is no data available on its prevalence at a national level. 3 Co-infection of hepatitis E and P. falciparum malaria are rarely reported in the literature. 4 This is the first reported case in Sri Lanka of a patient co-infected with both hepatitis E and P. falciparum malaria, and both infections were imported.…”
Section: Introductionmentioning
confidence: 99%